SELEKTIFITAS PERTUKARAN ION Mg-K AKIBAT PEMBERIAN LARUTAN NH3 PADA TANAH RENZINA DENGAN BEBERAPA WAKTU INKUBASI - Silahooy, Charles; Silahooy, Veince Benjamin; Huwae, Laury Marcia Ch (Pattimura University, 2022)
The cation exchange on the adsorbtion complex constitutes an important chemical character of soil in determining soil fertility level. To see which ion that more selective to be separated by NH4+ ion complex absorbtion between Mg and K. The expereiment was done at soil laboratory, faculty of agriculture, pattimura university ambon. The expereiment applied completely randomized desighn. With factorial pattern. NH3 solution treatment consist of 3 hour, 7 and 14 days. the result of the expereiment showed that there was an interaction between NH3 solution treatment and incubation time on the selectivity interchange of Mg-K ion, the availability rate of K and Mg, the change of pH and the conductivity of electricity . the addition of NH3 solution increased soil ph, DHL, Exchangable Mg, exchangeable k, Mg2+ and k+ ions in the soil solution and effected selectivity of Mg-k ion interchange.